Synthesis and characterization of N, O-donor Schiff base capped ZnS NPs as a sensor for fluorescence selective detection of Fe 3+, Cr 2+ and Cd 2+ ions - Dasari Ayodhya; Guttena Veerabhadram (Modern Electronic Materials, 2018)
We report the simple synthesis of zinc sulfide nanoparticles (ZnS NPs) by a co-precipitation method using Schiff base, (2-[(4-methoxy-phenylimino)-methyl]-4-nitro phenol) as a capping agent. Here, Schiff base is also used as N, O-donor ligand to control the morphology of NPs and fluorescence interactions. The formation of ZnS NPs and their optical, structural, thermal properties and morphologies were studied by means of UV–vis DRS, fluorescence, FTIR, XRD, SEM, TEM, zeta potential and TGA. The optical properties and quantum confinement effect of the products were confirmed by means of spectroscopic measurements. XRD and TEM image shows that the synthesized ZnS NPs have cubic structures with a diameter of about less than 10 nm. The prepared ZnS NPs exhibited as a selective probe detection of Fe3+, Cr2+ and Cd2+ ions by fluorometrically and the emission band which disappears in the presence of increasing concentrations of Fe3+, Cr2+ and Cd2+ ions. Based on the fluorescence quenching of the NPs in the presence of metal ion of interest, the feasibility of their determinations was examined according to the Stern-Volmer equation. Our work suggested that Schiff base capped ZnS NPs could be a potential selective sensor in the detection of heavy metal ions.